Survival of the Fittest: Why Terrorist Groups Endure - Joseph K. Young; Laura Dugan (Perspectives on Terrorism)
Why do terrorist groups endure? This question is relevant to scholars and policy makers alike. In the past, this issue was not been addressed in a systematic fashion. Recent work investigates this question using data on transnational groups and finds that factors associated with the home country can influence the duration the group endures. Applying the theory of outbidding to terrorist group survival, we argue that strategic competition among groups predicts group duration. Using the Global Terrorism Database, we develop a dataset using the terrorist group as the unit of analysis to model the duration of group activity and thus include the largest sample of groups yet. Controlling for previous explanations of both group duration and terrorism, we find a robust effect for the impact that group competition has on terrorist group survival.